A study on schedule management for BIM projects in the construction industry - Soon Ern, Peniel Ang; Ali, Roslinda; Yang, Ooi Chee (Penerbit Uthm, 2018)
There is an advance modelling tool that currently been pushed by the industry is BIM. BIM as known as Building Modelling Information is a computerized process that is used to design, understand and establish the key physical and functional characteristic of a building on a ‘virtual’ computerized model basis at its most basic level [4]. Basically the resulting model is a digital representation of the building which the data can be extracted and analyzed to generate information that can be used for decision making and enhance the process of delivering the building and the entire life cycle use of the building [4]. BIM implementation can help to improve the quality of project especially the schedule management. By implementing BIM into construction project, it can provides schedule visualization which can make the construction planning more efficient. Besides that, through the BIM model clash detection can be detected in the preconstruction phase which save a lot of time on rework during construction phase.